KELAYAKAN FINANSIAL DAN SALURAN PEMASARAN KELAPA SAWIT SEBAGAI KOMODITAS UNGGULAN DI KABUPATEN LAMPUNG TENGAH PROVINSI LAMPUNG - M . Irfan Affandi; Syafri Alfizar (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
Palm oil is one of the leading commodity in Lampung province that plays a role in the regiona leconomy and the income of farmers. The aims of this research are to find out(1) the financial feasibility and (2)marketing efficiency of palm oil. The research is conducted in Bangun Rejo and Bekri Subdistricts, Central Lampung Regency. The data is collected since April up to June 2016. . The population of palm oil farmers who have plants with the age of 5 up to 10 years in Binjaingagung 54 and Sidoluhur Villages are 118 inhabitants. Respectively the total population of oil palm farmers are 172 inhabitants. The sample in this research the oil palm farmers. The number of samples are 27 farmers out of is total population of 172 farmers. The analysis data methods used in this research are advantages, quantitative financial and marketing analyses. The results of this research show: (1) Palm oil farming in Central Lampung is financially feasible, (2) Marketing of oil palm in Central Lampung Regency are not efficient. It is showed by market structure that imperfectly compete. Market behavior of the farmers as the price taker and ratio profit margin are not equally distributed evenly spread.